Strengthening Regional Food Security: A Public Administration Approach to Agricultural Education and Sustainable Community Empowerment Frameworks - Syaharuddin Alrif; Jamaluddin Ahmad; Muh Rais Rahmat R; Ahmad Mustanir (Edumaspul: Jurnal Pendidikan, 2026)
Food security has become one of the most pressing global challenges due to population growth, climate change, and declining agricultural productivity. Agricultural education plays a strategic role in enhancing community capacity to develop sustainable food systems while promoting environmental awareness and socio-economic resilience. This study aims to develop a sustainable agricultural learning framework that strengthens regional food security through community empowerment. Using a qualitative case study approach, the research collected data through in-depth interviews, field observations, focus group discussions, and document analysis involving farmers, agricultural extension officers, educators, local government representatives, and community leaders. The findings reveal that integrating agricultural education with local wisdom, participatory learning, and sustainable farming practices significantly improves agricultural knowledge, innovation adoption, food production, and community participation. The proposed framework consists of five interconnected dimensions: agricultural literacy, sustainability-oriented learning, technological innovation, stakeholder collaboration, and community empowerment. These dimensions collectively contribute to improving household food security, strengthening local food systems, and fostering long-term agricultural resilience. The study highlights that agricultural education should move beyond knowledge transfer toward transformative learning that enables communities to become active agents of sustainable development. The proposed framework provides practical implications for policymakers, educational institutions, and rural development practitioners in designing education-based strategies to achieve regional food security and support the Sustainable Development Goals (SDGs), particularly SDG 2 (Zero Hunger), SDG 4 (Quality Education), and SDG 11 (Sustainable Cities and Communities).